Multimodal analgesia in the clinical examples or how it works - Dmytriiev, D. V.; Zaletsky, B. V. (Pain medicine, 2016)
The presented clinical cases and the multimodal analgesia scheme used in them suggests the effectiveness of anesthesia, which is achieved due to the possibility to influence on the peripheral mechanism of pain emergence. Regional analgesia can significantly reduce the need for opioids and their combination, and can restore the analgesic potential of the latter. Various mechanisms of action of these drugs make it possible to prescribe them in combination and in small doses in order to achieve a significant analgesic effect.